2010
DOI: 10.1002/mus.21727
|View full text |Cite
|
Sign up to set email alerts
|

Artificial perineurium to enhance nerve recovery from damage after neurolysis

Abstract: We have developed a novel biodegradable poly-lactide (PLA) film (honeycomb film) with a micropatterned porous structure on one side. We hypothesized that this film could be used as a substitute for perineurium. We used two types of thin PLA film: honeycomb film and cast film with smooth surfaces on both sides. In a rat extensive internal neurolysis model, the nerve was wrapped with honeycomb film (group H) or cast film (group CA), or left unwrapped (group C). Histological and functional analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In addition, the honeycomb film has a smooth surface on the other side that prevents adhesion between the nerve and surrounding tissues 12. Our previous study confirmed that the honeycomb film can provide a perineurial barrier function and thus potentially expand the indications of internal neurolysis, a procedure for which the advantages and disadvantages remain controversial 16…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, the honeycomb film has a smooth surface on the other side that prevents adhesion between the nerve and surrounding tissues 12. Our previous study confirmed that the honeycomb film can provide a perineurial barrier function and thus potentially expand the indications of internal neurolysis, a procedure for which the advantages and disadvantages remain controversial 16…”
Section: Discussionmentioning
confidence: 59%
“…Our previous study demonstrated that the honeycomb film not only prevented adhesion, but also compensated for the loss of perineurial barrier function. This enhanced functional recovery even after extensive internal neurolysis, a procedure that significantly damages the microvascular system within the epineurium 16. We therefore believe that wrapping with a thin, malleable, bioadhesive, biodegradable material like the honeycomb film is better than bridging the transected nerve ends using a thick, hard tubular material.…”
Section: Discussionmentioning
confidence: 98%
“…Electrical pulses (supramaximal; duration, 100 ms; frequency, 1 Hz; square wave) were applied with an isolator (SS-201J; Nihon Kohden) connected to an electronic stimulator. CMAPs were recorded to estimate electrophysiological function and evaluate MCV [47], [48].…”
Section: Methodsmentioning
confidence: 99%
“…Scarring and adhesion represent major challenges following injury and surgical procedures of peripheral nerves, often leading to pain and even nerve dysfunction. Currently, the removal of the surrounding scar tissue (external neurolysis) up to the resection of the epifascicular fraction of the epineurium (internal neurolysis) is the most common treatment ( Mazal and Millesi, 2005 ; Okui et al, 2010 ; Frykman et al, 1981 ; Sakurai and Miyasaka, 1986 ; Calfee et al, 2008 ). However, clinical symptoms recur in most patients owing to re-appearing secondary perineural adhesions and neural fibrosis ( Abe et al, 2005 ; Botte et al, 1996 ; Dam-Hieu et al, 2005 ; Frykman et al, 1981 ; Ohsumi et al, 2005 ; Robertson, 1996 ; Rydevik et al, 1976 ), resulting in impaired nerve function ( Lundborg, 2003 ; Ngeow, 2010 ; Ohsumi et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical symptoms recur in most patients owing to re-appearing secondary perineural adhesions and neural fibrosis ( Abe et al, 2005 ; Botte et al, 1996 ; Dam-Hieu et al, 2005 ; Frykman et al, 1981 ; Ohsumi et al, 2005 ; Robertson, 1996 ; Rydevik et al, 1976 ), resulting in impaired nerve function ( Lundborg, 2003 ; Ngeow, 2010 ; Ohsumi et al, 2005 ). Therefore, several different therapeutic approaches have been tested ( Doi et al, 1992 ; Varitimidis et al, 2001 ; Wintsch and Helaly, 1986 ), including implantation of muscle flaps, fat grafts ( De Smet and Vandeputte, 2002 ; Bernsmann et al, 2001 ) or diverse biomaterials ( Dam-Hieu et al, 2005 ; Ikeda et al, 2003 ; Ohsumi et al, 2005 ; Petersen et al, 1996 ; Wang et al, 1998 ), yet most therapies are still experimental and none are routinely used on patients ( Atkins et al, 2006 ; Ngeow, 2010 ; Okui et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%